Recent advancement challenges with synthesis of biocompatible hemodialysis membranes. (November 2022) - Zaman, Shafiq Uz; Rafiq, Sikander; Ali, Abulhassan; Mehdi, Muhammad Shozab; Arshad, Amber; Rehman, Saif-ur; Muhammad, Nawshad; Irfan, Muhammad; Khurram, Muhammad Shahzad; Zaman, Muhammad Khaliq U.; Hanbazazah, Abdulkader S.; Lim, Hooi Ren; et al.
Abstract: The focus of this study is to enhance the protein fouling resistance, hydrophilicity, biocompatibility, hemocompatibility and ability of the membranes and to reduce health complications like chronic pulmonary disease, peripheral vascular disease, cerebrovascular disease, and cardiovascular disease after dialysis, which are the great challenges in HD applications. In the current study, the PSF-based dialysis membranes are studied broadly. Significant consideration has also been provided to membrane characteristics (e.g., flowrate coefficient, solute clearance characteristic) and also on commercially available polysulfone HD membranes. PSF has gained a significant share in the development of HD membranes, and continuous improvements are being made in the process to make high flux PSF-based dialysis membranes with enhanced biocompatibility and improved protein resistance ability as the major issue in the development of membranes for HD application is biocompatibility. There has been a great increase in the demand for novel biocompatible membranes that offer the best performances during HD therapy, for example, low oxidative stress and low change ability of blood pressure. Graphical abstract: Image 1 Highlights: Critical analysis of hemodialysis membranes has been discussed. Modification methodology has been critically analyzed. Biocompatibility and fouling issue have been measured in membrane. Biocompatible membranes offers best performances during HD therapy.